2016
DOI: 10.1002/chem.201504958
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanotube Tailored Fabrication of Uniquely Shaped Polydopamine Nanofibers as Photothermal Converters

Abstract: Helically coiled and linear polydopamine (PDA) nanofibers were selectively fabricated with two different types of lipid nanotubes (LNTs) that acted as templates. The obtained coiled PDA-LNT hybrid showed morphological advantages such as higher light absorbance and photothermal conversion effect compared to a linear counterpart. Laser irradiation of the coiled PDA-LNT hybrid induced a morphological change and subsequent release of the encapsulated guest molecule. In cellular experiments, the coiled PDA-LNT effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…An interesting example of template directed synthesis is the formation of capped, coiled fibers through dopamine polymerization in the presence of lipid nanotubes. Dopamine deposition in this instance occurs preferentially in lipid ribbon boundaries, along helical seams and at the ends of the tubes ( Figure ) …”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 95%
See 2 more Smart Citations
“…An interesting example of template directed synthesis is the formation of capped, coiled fibers through dopamine polymerization in the presence of lipid nanotubes. Dopamine deposition in this instance occurs preferentially in lipid ribbon boundaries, along helical seams and at the ends of the tubes ( Figure ) …”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 95%
“…TEM image of polydopamine deposited onto lipid nanotubes in helical seams and at tube ends. Reproduced with permission . Copyright 2010, the American Chemical Society.…”
Section: Catecholamine Polymers: Chemistry and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…They have now been widely applied in many areas, such as electrochemical sensors, electro‐optical and electro‐chromic devices, field‐effect transistors, light‐emitting diodes and so on . Recent research demonstrated that polydopamine and other synthetic eumelanins with 1D structures showed unique optical and electric properties (e. g. unique biooptoelectronic property, higher light absorbance and higher photothermal conversion effect) different to those of their spherical counterparts, which apparently simulate scientists to explore new synthetic routes for 1D polydopamine colloidal materials ,…”
Section: Polydopamine Based Colloidal Materialsmentioning
confidence: 99%
“…The polydopamine nanotubes obtained exhibit good formaldehyde sensing properties. Ding et al have demonstrated helically coiled and linear polydopamine nanofibers generated by using lipid nanotubes (LNTs) as templates . Coiled PDA‐LNT nanofibers showed higher light absorbance and photothermal conversion effect compared to linear nanofibers.…”
Section: The Modulation Of Melanin‐like Materialsmentioning
confidence: 99%